Relationship between long covid and functional disability in adults and the seniors in the south of Brazil - Yohana Pereira Vieira; Luan Nascimento da Silva; Bruno Pereira Nunes; Tatiane Nogueira Gonzalez; Suele Manjourany Silva Duro; Mirelle de Oliveira Saes (BMC Public Health)
Abstract Background Individuals living with long COVID experience a range of symptoms that affect their ability to carry out daily activities or participate in social and community life. This study aimed to analyze association between functional disability and the occurrence of long COVID symptoms, as well as to analyze the effect of symptom persistence time on functional disability. Methods This is a cross-sectional study using data from the SulCovid-19 study, which interviewed individuals who had COVID-19 between December 2020 and March 2021. The functional disability outcome was assessed using the Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL) scales, while the exposures were the symptoms of long COVID. Adjusted analyses between outcomes and exposures, stratified by time after the acute phase of infection, were performed using Poisson regression with robust variance adjustment. Results The prevalence of BADL disability was 4.8% (95%CI 4.0;5.6), and for IADL disability, it was 8.4% (95%CI 7.4;9.4). The main symptoms associated with BADL disability were dyspnea, dry cough and sore throat, while for IADL, they were joint pain, muscle pain, loss of sensation, nasal congestion, sore throat and runny nose. When stratified by tertiles of time after the acute phase of infection, a relationship was found between BADL disability and dyspnea, ageusia and, nasal congestion in the 3rd tertile, while only ageusia was found to be related to IADL disability in the 3rd tertile. Conclusions Long COVID symptoms were associated wiht limitations in the functional capacity of adults and the seniors. The findings can be used to guide the care and rehabilitation of individuals with disabilities who have had COVID-19, particularly for referral to appropriate health professionals.